Analisis Perencanaan Karier Berdasarkan Kompetensi Mahasiswa Pada Mahasiswa Program Studi Pendidikan Akuntansi Fakultas Keguruan Dan Ilmu Pendidikan Universitas Muhammadiyah Surakarta Angkatan 2014 - ULFAH, ROFIQOH FITRIA, Drs. Budi Sutrisno, M.Pd (2017)
This research aim to determine: first, career planning prepared by students. Second, to know what the factors of career planning influenced by students. This type of research is a qualitative approach to ethnography. The object of this research is Accounting Education of Muhammadiyah University of Surakarta which workplace of SMK Negeri 1 Banyudono Boyolali and Department Education of Youth and Sports of Surakarta. The competency students profile of Accounting Education force 2014 is divided into 12 criteria that is based on high IPK, medium IPK, low IPK, followed organization and work part time or not. The results of this research showed that nine of students have correct planned of their careers because they are taken based on their majors for example to become a teacher and entrepreneurship, one of student does not correct planned with his career because they are not taken based on their majors that is to be accounting and entrepreneurship whereas two other students have not career planning. The factors of career planning influenced by students there are seven things, including the interest and talent, parents, environment, basic majors, gender, opportunities and salary.